Ordenanza que regule los decibeles y evite la contaminación auditiva en personas discapacitadas en el cantón Babahoyo - Velasco Camacho, María Guadalupe (2025)
The research is about creating an ordinance that regulates the decibels and prevents noise pollution in disabled people in the Babahoyo canton, with the general objective of creating an ordinance that regulates the decibels and prevents noise pollution in disabled people to protect them from noise pollution in the Babahoyo canton. For a better analysis of the research as indicated by the methodology was divided into 3 chapters; Chapter I is developed by the theoretical framework in which are the theoretical bases, comparative law and doctrine of the investigated problem, in turn this chapter was divided into 3 sections in the first one is developed on the background, ordinances, municipal law and national regulations; in the second section the constitutional principles such as equality, accessibility, participation, inclusion, human dignity, equity, solidarity and social function in addition to the linked constitutional rights were developed; in the third section the comparative legislation of Latin American countries such as Colombia, Mexico, Chile, Argentina and Brazil was dealt with; accompanied by the analysis of international instruments with the treaties ratified with Ecuador; within Chapter II, the methodological framework was addressed, in which the instruments and techniques used are detailed as well as the development of the questionnaire and the survey and the viability that it grants to the proposal through the results within Chapter III in which the propositional framework was addressed in which the normative parameters contained in the Ordinance that regulates the decibels and prevents noise pollution in disabled people in the Babahoyo canton were made.